2011
DOI: 10.1007/s11284-011-0830-7
|View full text |Cite
|
Sign up to set email alerts
|

Advances in first bloom dates and increased occurrences of yearly second blooms in eastern China since the 1960s: further phenological evidence of climate warming

Abstract: Advances in first bloom dates and increased occurrences of yearly second blooms in eastern China since the 1960s: further phenological evidence of climate warming Abstract Confirming the results of previous regional studies on changes in first bloom dates (FBD) in China, this study provides evidence that complements conclusions drawn from studies of phenological changes in other dynamic climate systems in the Northern Hemisphere. Furthermore, increased occurrences of yearly second blooms (YSB) further reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…over the period 1952-2007 were nearly −1.1 days/decade in Henan, −2.0 days/decade in Beijing and Shandong, and −1.4 days/decade in Shaanxi. Furthermore, the first flowering dates of 23 species at 22 stations in eastern China since the 1960s were found to advance at the average rate of 1.2 days/decade [35], and the same rate has been reported for the FLD across the Northern Hemisphere over the period 1955-2002 [36]. The two results are also in good agreement with the average trend (−1.3 days/decade) of Zhongyuan Peony.…”
Section: The Consistency Of Regional Phenological Trendssupporting
confidence: 82%
“…over the period 1952-2007 were nearly −1.1 days/decade in Henan, −2.0 days/decade in Beijing and Shandong, and −1.4 days/decade in Shaanxi. Furthermore, the first flowering dates of 23 species at 22 stations in eastern China since the 1960s were found to advance at the average rate of 1.2 days/decade [35], and the same rate has been reported for the FLD across the Northern Hemisphere over the period 1955-2002 [36]. The two results are also in good agreement with the average trend (−1.3 days/decade) of Zhongyuan Peony.…”
Section: The Consistency Of Regional Phenological Trendssupporting
confidence: 82%
“…Using the spring indices (SI) model, Schwartz et al [40] found FLD advanced quickly over 1955-2002 at a rate of 1.2 days/decade across the Northern Hemisphere. Ge et al [41] reported that the average trend for the first flowering date of 23 species at 22 sites in China was 1.2 days/decade, implying a 6 days' advance during the past 50 years. Results of this study (1.1 days/decade) and those by Ge et al [41] indicated that changes of spring phenophases in China was close to the Schwartz's results, but weaker than other studies [38,39].…”
Section: Regional Differences Of Phenological Trendsmentioning
confidence: 99%
“…Ge et al [41] reported that the average trend for the first flowering date of 23 species at 22 sites in China was 1.2 days/decade, implying a 6 days' advance during the past 50 years. Results of this study (1.1 days/decade) and those by Ge et al [41] indicated that changes of spring phenophases in China was close to the Schwartz's results, but weaker than other studies [38,39]. The numerical difference of phenological changes among above studies may be related to datasampling methodologies, different definitions of the phenological events and the distribution of the study sites, and the actual difference of phenologial change.…”
Section: Regional Differences Of Phenological Trendsmentioning
confidence: 99%
“…; Ge et al . ). The ascending order of grassland NPP and its class may have significant implications for grassland succession in Chinese grassland ecosystems with predicted changes in spatio‐temporal patterns of precipitation under the influence of global climate change.…”
Section: Discussionmentioning
confidence: 97%